Modern elementary particle physics - Kane, Gordon (Cambridge: Cambridge University Press, 2017)
"Written for students and scientists wanting to learn about the Standard Model of particle physics. Only an introductory course knowledge about quantum theory is needed. This text provides a pedagogical description of the theory, and incorporates the recent Higgs boson and top quark discoveries. With its clear and engaging style, this new edition retains its essential simplicity. Long and detailed calculations are replaced by simple approximate ones. It includes introductions to accelerators, colliders, and detectors. Several main experimental tests of the Standard Model are explained. Descriptions of some well-motivated extensions of the Standard Model prepares the reader for new developments. It emphasizes the concepts of gauge theories and Higgs physics, electroweak unification and symmetry breaking, and how force strengths vary with energy, provides a solid foundation for those working in the field, and for those who simply want to learn about the Standard Model"--
Relativistic notation, Lagrangians, and interactions -- Gauge invariance -- Non-abelian gauge theories -- Dirac notation for spin -- The Standard Model Lagrangian -- The electroweak theory and quantum chromodynamics -- Masses and the Higgs mechanism -- Cross sections, decay widths, and lifetimes; W and Z decays -- Production and properties of W± and Z-- Measurement of electroweak and QCD parameters; the muon lifetime -- Accelerators - present and future -- Experiments and detectors -- Low energy and non-accelerator experiments -- Observation of the Higgs boson at the CERN LHC; is it the Higgs boson? -- Colliders and tests of the Standard Model; particles are point-like -- Quarks and gluons, confinement and jets -- Hadrons, heavy quarks, and strong isospin invariance -- Coupling strengths depend on momentum transfer and on virtual particles -- Quark (and lepton) mixing angles -- CP violation -- Overview of physics beyond the Standard Model -- Grand unification -- Neutrino masses -- Dark matter -- Supersymmetry.
Includes bibliographical references and index.
Keywords: Particles (Nuclear physics); Standard model (Nuclear physics); Quarks; Leptons (Nuclear physics)